Efficacy of water-in-diesel emulsion to reduce exhaust gas pollutants of diesel engine - Abdul Karim, Z.A. (Asian Research Publishing Network, 2016)
The influence of engine loads of a single cylinder diesel engine on engine performance and exhaust emissions when using water-in-diesel fuels were experimentally studied in this work. The work aims to determine the parameter that influence pollutants reduction capability of emulsified fuel at different engine loads and to ascertain the type of fuel blend for optimum engine performance. Physical characterization analyses were performed on 16 stable WiDE samples to evaluate the viscosity, the density and the water droplet size of each sample with various water content, hydrophiliclipophilic balance values and surfactant percentages. The analyses revealed that only a few samples satisfy the CWA15145 requirements. Hence, this paper only discusses the results of engine performances and emission measurements when using 4 types of emulsified fuels, i.e. percentage of water content of 9, 12, 15 and 18 with HLB value of 6.31 and surfactant percentage of 10 volume of water. Engine torque, fuel consumption and exhaust emissions were recorded and analysed from the engine operating at a speed of 2600 rpm, with variation of engine load between 0 to 100 percent. The results showed that in general, no significant change in brake power was observed but there was a prominent reduction in nitrogen oxides (NOx). The average nitrogen oxides emission was observed to be reduced by 40 percent for WiDE-12 compared to the B5 diesel fuel. The average brake power for WiDE-12 has slightly improved by 5 percent compared to the B5 diesel. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.